MODEL PEMBELAJARAN OSBORN UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Nurafifah, Luthfiyati; Nurlaelah, Elah; Usdiyana, Dian (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2016)
The purpose of this research is to find out the increase of student’s mathematical problem solving competence through the implementation of Osborn Learning Model, as well as compare it with the student who earned conventional learning. In addition, the purpose of this research is to find out the increase of mathematical problem solving competence on a group of student with high, middle, and low capability. The next purpose is to find out the attitude of the students against the osborn learning model. Methods used in this research is quasi Experimenter Method with pretest and post-test Marginalized Control Design. Population on this research are all of students of VIII grades in SMPN 1 Bandung. Samples on this research are two classes of VIII grades, one class as Experimental Class and the other one as control class. Research data obtained through the test of student’s mathematical problem solving competence, questionnaire, and observation sheets. The result of this research shows that the increasing of student’s mathematical problem solving competence with Osborn Learning Model better than the increasing of student’s mathematical problem solving competence with conventional learning. There are differences in the increasing competence on the groups of high capability, middle capability and low capability in osborn class and conventional class. In general, the students give a positive attitude against Osborn Learning Model.